A poor perspective of self weight significantly increases adverse outcomes in non-alcoholic fatty liver disease (NAFLD) - Fu, Clarissa Elysia; Ng, Cheng Han; Chew, Nicholas W. S.; Heng, Zane En Qi; Chin, Yip Han; Quek, Jingxuan; Lim, Wen Hui; Xiao, Jieling; Chan, Kai En; Tan, Darren Jun Hao; Tan, Caitlyn; Zhang, Sitong; et al. (Frontiers in Medicine, 2022)
Background: Non-alcoholic fatty liver disease (NAFLD) is prevalent amongst overweight and obese individuals, and weight loss remains the main mode of treatment for NAFLD patients. Weight perception plays a key role in the efficacy of such treatment. The current study aims to investigate the prevalence, associating factors and implications of poor weight perception amongst such individuals. Methods: An analysis was done on data collected from NHANES between 1999-2018. Comparison was made between NAFLD individuals with and without poor weight perception in terms of prevalence, associated characteristics, and clinical outcomes. Multivariate analysis was used to compare effect size of adverse events associated with NAFLD individuals with poor weight perception. Results: Of the 12,170 NAFLD patients, 19.2% (CI:18.5% to 19.9%) had poor weight perception. Poor weight perception was significantly associated with lower education levels, reduced levels of exercise and unhealthier lipid profiles. There was an increased risk in all-cause mortality (HR: 1.18, CI: 1.00 to 1.38, p=0.047), cardiovascular disease mortality (SHR: 1.33, CI: 1.03 to 1.71, p=0.026), major adverse cardiovascular events (OR: 1.21 CI: 1.10 to 1.32, p<0.001), and advanced fibrosis (OR: 1.30, CI: 1.03 to 1.64, p=0.025) for individuals with poor weight perception. Conclusion: This study highlights the positive association between appropriate weight perception and better outcomes in individuals with NAFLD. Poor weight perception increased the risk of adverse events and decreased inclination towards seeking weight loss treatment. Greater emphasis should be placed on dealing with weight perception in individuals with NAFLD for better treatment outcomes.